Mastering 3D printing : a guide to modeling, printing, and prototyping - Horvath, Joan C. (Apress, 2020)
"Get the most out of your printer, including how to design models, choose materials, work with different printers, and integrate 3D printing with traditional prototyping to make techniques like sand casting more efficient. This book is for new 3D printer owners, makers of all kinds, entrepreneurs, technology educators, and anyone curious about what you can do with a 3D printer. In this revised and expanded new edition of Mastering 3D Printing, which has been a trusted resource through five years of evolution in the 3D printing industry, you'll gain a comprehensive understanding of 3D printing. This book presumes no foreknowledge and describes what you need to know about how printers work, how to decide which type of printer (filament, resin, or powder) makes the most sense for you, and then how to go forward in the case of filament and resin printers. This new edition now includes material about consumer resin printing, the evolution of lower-cost metal printing, and the plethora of both materials and applications. What You'll Learn; Choose among the different 3D printing technologies; Create or find 3D models to print; Make both easy and challenging prints come out as you imagined; Assess whether your business, factory, home or classroom will benefit from 3D printing; Work with applications that are good candidates for first projects in home and industrial applications. Who This Book Is For: People who are encountering 3D printing for the first time, or for those who want to level up their skills. It is designed for the nontechnical adult and minimizes jargon. However more sophisticated users will still find tips and insights of value."